1981
DOI: 10.1152/jappl.1981.51.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular tone improves VA/Q matching in obliterative pulmonary hypertension

Abstract: We have studied the influence of pulmonary vascular tone on ventilation-perfusion relationships in subjects with chronic obliterative pulmonary vascular disease. We administered oxygen, isoproterenol, or nitroprusside on 15 occasions in 7 subjects and observed a fall in pulmonary vascular resistance of greater than 15% in 8 of these 15 trials. When pulmonary vascular resistance was reduced, there was an increase in the perfusion of lung units with low ventilation-perfusion ratios (VA/Q) and/or shunt as determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 0 publications
3
18
0
1
Order By: Relevance
“…165 Some researchers have suggested that maintaining pulmonary vascular tone could improve V-Q matching in these conditions and have advocated against mitigating the existing vascular tone by vasodilators. In order to decide whether potent vasodilators are use- Figure 6.…”
Section: What Is the Temporal Pattern Of Ph After Apte?mentioning
confidence: 99%
“…165 Some researchers have suggested that maintaining pulmonary vascular tone could improve V-Q matching in these conditions and have advocated against mitigating the existing vascular tone by vasodilators. In order to decide whether potent vasodilators are use- Figure 6.…”
Section: What Is the Temporal Pattern Of Ph After Apte?mentioning
confidence: 99%
“…(Walmrath et al, 1997) Calcium channel blockers (BarberĂĄ andBlanco, 2009) Salbutamol i.v. (Ballester et al, 1989) High fraction of inhaled oxygen (Dantzker and Bower, 1981;Ballester et al, 1989) Inhaled salbutamol in patients with COPD and exacerbation (Polverino et al, 2007) Isoproterenol (Dantzker and Bower, 1981) Nitroprusside (Dantzker and Bower, 1981) Inhaled fenoterol high dose (Viegas et al, 1996) Aminophylline i.v. (BarberĂĄ et al, 1992) Sildenafil p.o.…”
Section: General Aspectsmentioning
confidence: 99%
“…Also, in the presence of the increased pulmonary vascular resistance and advanced pulmonary vascular lesions, such as those described in Eisenmenger syndrome (21), perfusion distribution abnormalities in the perfusion distribution are expected. To our knowledge, the / distribution in the lungs of patients with Eisenmenger's syndrome as well as the effect of body position changes on this / distribution has not been prospectively studied, but as mentioned above, abnormalities in / distribution are likely to be present in these patients and they are also likely to be modified as a result of pulmonary hemodynamic changes (i.e., changes in cardiac output and pulmonary vascular resistance with position), as it has been shown in other human models of chronic obliterative pulmonary vascular disease (22,23).…”
Section: Pathophysiologic Mechanismmentioning
confidence: 99%